2007
DOI: 10.1051/0004-6361:20065825
|View full text |Cite
|
Sign up to set email alerts
|

Lyα emission in high-redshift galaxies

Abstract: Context. A significant fraction of the high-redshift galaxies show strong Lyα emission lines. For redshifts z > 5, most known galaxies belong to this class. However, so far not much is known about the physical structure and nature of these objects. Aims. Our aim is to analyse the Lyα emission in a sample of high-redshift UV-continuum selected galaxies and to derive the physical conditions that determine the Lyα profile and the line strength. Methods. VLT/FORS spectra with a resolution of R ≈ 2000 of 16 galaxie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
124
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(143 citation statements)
references
References 61 publications
17
124
2
Order By: Relevance
“…Additionally, a double peaked Lyα emission line profile was found from the starburst galaxy T1214-277 by Mas-Hesse et al (2003), who concluded that the feature is caused by emission in an outflow. Double-peaked Lyα profiles have been observed also at redshift z ∼ 3, in spectra of star forming galaxies (Fosbury et al 2003;Christensen et al 2004;Venemans et al 2005;Tapken et al 2007).…”
Section: Individual Notesmentioning
confidence: 88%
“…Additionally, a double peaked Lyα emission line profile was found from the starburst galaxy T1214-277 by Mas-Hesse et al (2003), who concluded that the feature is caused by emission in an outflow. Double-peaked Lyα profiles have been observed also at redshift z ∼ 3, in spectra of star forming galaxies (Fosbury et al 2003;Christensen et al 2004;Venemans et al 2005;Tapken et al 2007).…”
Section: Individual Notesmentioning
confidence: 88%
“…Haro 2 also shows an UV continuum luminosity similar to that of the weakest Lyman Break Galaxies (LBGs) in the redshift range z = 2.7−5 (Tapken et al 2007). This fact, together with its high Notes.…”
Section: Introductionmentioning
confidence: 86%
“…The emission is symmetric, in contrast to the asymmetric line profile characteristic of Lyman break galaxies (LBGs; Tapken et al 2007). This indicates that there is no H i gas in front of the emitting region to absorb the emitted Lyα photons.…”
Section: Position and Profile Of The Emission Linementioning
confidence: 98%